2011
DOI: 10.1503/cjs.000910
|View full text |Cite
|
Sign up to set email alerts
|

Average 10.1-year follow-up of cementless total knee arthroplasty in patients with rheumatoid arthritis

Abstract: Background: Total knee arthroplasty (TKA) using a cemented technique has been recommended in patients with rheumatoid arthritis owing to the initial stability of the fixation and long-term durability of the components; however, similar long-term follow-up results have been reported in patients who have undergone cementless TKA. The purpose of this study was to evaluate the radiologic and clinical outcomes of cementless TKA in patients with rheumatoid arthritis. Methods:We enrolled patients undergoing cementles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 27 publications
1
12
0
3
Order By: Relevance
“…Eskola et al 74 studied 42 patients with rheumatoid arthritis, and although there was one revision due to ligamentous laxity and two patients had radiolucencies of more than 2 mm, the authors found no clinically-evident loosening in cementless knees in this group of patients. Woo et al 75 reported 179 rheumatoid arthritic knees with a mean follow-up of 10.1 years and estimated the 15.5 year survivorship of this fully cementless TKA group to be 96.8%.…”
Section: Cementless Tkamentioning
confidence: 99%
“…Eskola et al 74 studied 42 patients with rheumatoid arthritis, and although there was one revision due to ligamentous laxity and two patients had radiolucencies of more than 2 mm, the authors found no clinically-evident loosening in cementless knees in this group of patients. Woo et al 75 reported 179 rheumatoid arthritic knees with a mean follow-up of 10.1 years and estimated the 15.5 year survivorship of this fully cementless TKA group to be 96.8%.…”
Section: Cementless Tkamentioning
confidence: 99%
“…При анализе исходов лечения 112 больных рев-матоидным артритом, которым было выполне-но 179 артропластик с минимальным периодом наблюдения 10,1 лет, 15-летняя выживаемость бесцементных имплантатов, по данным Y.K. Woo с соавторами, составила 96,8% [63].…”
Section: результаты артропластикиunclassified
“…25,26 Recently, studies have reported increased longevity and improved implant fixation and bone stock with the emergence of newer biomaterials and implant designs. 25,[27][28][29][30][31][32] Cementless fixation depends on bone apposition to the implant's surface, and the biologic fixation between the bone and metal may result in improved longterm results. 26,27 However, there have been concerns regarding the bony fixation in elderly patients, 15,33 which may be due to decreased bone remodeling that occurs with normal aging.…”
mentioning
confidence: 99%